Insomnia Really Hurts: Effect of a Bad Night's Sleep on Pain Increases With Insomnia Severity - Wei, Yishul; Blanken, Tessa F.; Van Someren, Eus J. W. (Frontiers in Psychiatry, 2018)
Insomnia and chronic pain are highly prevalent conditions and are often comorbid. Somatic complaints other than pain are also often observed in insomnia. Poor sleep and pain are known to mutually reinforce each other. However, it is unknown whether the habitual severity of insomnia modulates the acute effect of a particularly bad night’s sleep on the next day’s pain severity, nor whether it modulates the acute effect of pain on the following night’s sleep quality. Using data from 3508 volunteers (2684 female, mean age 50.09 y), we addressed these questions in addition to the associations between the habitual severity of insomnia, somatic complaints, and pain. Results indicated that people suffering from more severe habitual insomnia showed stronger mutual acute within-day reactivity of pain and poor sleep quality. The same increased reactivity was found in people with more severe habitual pain. Interestingly, the acute within-day mutual reactivity of pain and poor sleep quality showed consistent asymmetry. Pain worsened more after a particular bad night’s sleep than it improved after a particularly good night’s sleep. Likewise, sleep worsened more after a day with more-than-usual pain than it improved after a day with less-than-usual pain. Future interventions may profit from addressing this asymmetric mutual reactivity especially in people with severe comorbid insomnia and chronic pain.